2019
DOI: 10.19041/apstract/2019/3-4/9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of credit access of cocoa farmers

Abstract: Access to credit is one of the critical areas that are of prime interest to development practitioners, agribusiness entrepreneurs and agricultural economists, mainly access to credit by farmers in order to increase their production and also reduce poverty. This study sought to analyze the determinants of credit access among cocoa farmers in the Asunafo North of the Ahafo Region of Ghana. The multistage sampling procedure was used to collect data from 100 cocoa farmers with the aid of a questionnaire. Sources o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
4
1
Order By: Relevance
“…This finding contrasts the work of Ref. [ 67 ], which stated that older farmers’ probability of securing credit is higher.…”
Section: Findings and Discussioncontrasting
confidence: 99%
“…This finding contrasts the work of Ref. [ 67 ], which stated that older farmers’ probability of securing credit is higher.…”
Section: Findings and Discussioncontrasting
confidence: 99%
“…Applying multiple linear regression analysis on data collected from 100 cocoa farmers in the Ahafo Region of Ghana, Mensah et al (2019) observed that farmers' age, marital status, educational level, farming experience, and family size significantly influenced access to credit. High-interest rates and the need for a guarantor were key negative determinants of access to credit.…”
Section: Review Of the Determinants Of Microcredit Accessmentioning
confidence: 99%
“…Access to credit for farmers is an issue of interest to agribusiness entrepreneurs, agricultural economists, and development practitioners. This is no surprise, given the truism that access to credit can increase farm productivity, market integration, and poverty reduction (Mensah et al, 2019;Alhassan et al, 2020). Microfinance was originally conceived as a suitable alternative source of financial services for the poor (currently estimated at over 2 billion people), who lack adequate collateral to access similar services in formal financial institutions, such as Banks (Thunstrom, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates an increase in size of family increases likelihood of a farmer getting access to finance. Mensah, et al (2019) concluded in the study that marital status, education, practice, age and family magnitude are the key aspects that prejudiced the farmer's capacity to admittance finance in the research in Asunafo North District, Ahafo Region.…”
Section: Introductionmentioning
confidence: 99%